Shifting shape, shaping text : philosophy and folklore in the Kōan - Heine, Steven, 1950- (University of Hawai'i Press, 1999)
Shifting Shape, Shaping Text examines the fox koan in relation to philosophical and institutional issues facing the Ch'an/Zen tradition in both Sung China and medieval and contemporary Japan.